Damage assessment of catwalks following the 2016 Kaikōura earthquake. (December 2020) - Yazdanian, Mohsen; Ingham, Jason; Kahanek, Christopher; Dizhur, Dmytro
Abstract: The 2016 Kaikōura earthquake (New Zealand, Mw 7.8) caused substantial financial losses to the Marlborough region wine industry. Following this earthquake, damage assessments were conducted for five wineries in the Marlborough region in order to identify the detailed damage data for wine tanks and catwalks. In this research, analysis of earthquake damage data related to catwalks for tanks and key recommendations related to catwalks for wine industry are presented. A critique of the collected data revealed that 58% and 24% of wine tanks in the inventory had catwalks that were tank-supported and self-supported, respectively, with the remaining 18% of wine tanks having either no catwalk or unclear catwalk supporting conditions. It was also noted that almost 50% of legged wine tanks had self-supported catwalks, while the majority (74%) of flat-based tanks had tank-supported catwalks. Due to the large number of flat-based tanks with tank-supported catwalks and the poor performance of tank-supported catwalks in the 2016 earthquake, the barrel part of wine tanks sustained the most frequent type of damage among the different tank parts. Based on analysis of earthquake-related damage data it was established that 25% of tank-supported catwalks sustained damage, while only 1% of self-supported catwalks sustained damage. Review of damage data revealed that the earthquake performance of tank-supported catwalks is dependent on the seismic performance of the system used to anchor flat-based tanks to the ground, and for the case of legged tanks the seismic performance of the tank legs and frame was identified as the most significant parameter affecting the performance of tank-supported catwalks.